Peranan Pasar Modal dalam Perekonomian Ummat Islam - Romi Adetio Setiawan (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2015)
Many Indonesian people are still hesitant and worried about the safe and lawful when they want to invest in capital markets, even though the Majelis Ulama Indonesia (MUI) has issued a fatwa on the application of Islamic principles in trade mechanism equity securities in the regular market Stock Exchange Number 80 of 2011, but there are many opinions that say that investing in the stock market at the stock exchange was unclean. The capital market is one of the important pillars of the world economy today. Many industries and companies that use capital market institutions as a medium to absorb investment and media to strengthen its financial position. The modern economy would not exist without the capital market that is well-organized. Every day trillions of rupiah transaction through this institution, this is what brings the authors to examine how the laws of sharia stock exchanges in the Islamic perspective.